A Framework for Screening and Classifying Obstructive Sleep Apnea Using Smartphones - Al-Mardini, Mamoun (2013)
A Master of Science thesis in Computer Engineering by Mamoun Al-Mardini entitled, "A Framework for Screening and Classifying Obstructive Sleep Apnea Using Smartphones," submitted in June 2013. Thesis advisor is Dr. Fadi Aloul and Co-advisor is Dr. Assim Sagahyroon. Available are both soft and hard copies of the thesis.